A screening program to test and treat for Helicobacter pylori infection: Cost-utility analysis by age, sex and ethnicity - Andrea M. Teng; Giorgi Kvizhinadze; Nisha Nair; Melissa McLeod; Nick Wilson; Tony Blakely (BMC Infectious Diseases, 2017)
Abstract Background The World Health Organization recommends all countries consider screening for H. pylori to prevent gastric cancer. We therefore aimed to estimate the cost-effectiveness of a H. pylori serology-based screening program in New Zealand, a country that includes population groups with relatively high gastric cancer rates. Methods A Markov model was developed using life-tables and morbidity data from a national burden of disease study. The modelled screening program reduced the incidence of non-cardia gastric cancer attributable to H. pylori, if infection was identified by serology screening, and for the population expected to be reached by the screening program. A health system perspective was taken and detailed individual-level costing data was used. Results For adults aged 25–69 years old, nation-wide screening for H. pylori was found to have an incremental cost of US$196 million (95% uncertainty interval [95% UI]: $182–$211 million) with health gains of 14,200 QALYs (95% UI: 5,100–26,300). Cost per QALY gained was US$16,500 ($7,600–$38,400) in the total population and 17% (6%-29%) of future gastric cancer cases could be averted with lifetime follow-up. A targeted screening program for Māori only (indigenous population), was more cost-effective at US$8,000 ($3,800–$18,500) per QALY. Conclusions This modeling study found that H. pylori screening was likely to be cost-effective in this high-income country, particularly for the indigenous population. While further research is needed to help clarify the precise benefits, costs and adverse effects of such screening programs, there seems a reasonable case for policy-makers to give pilot programs consideration, particularly for any population groups with relatively elevated rates of gastric cancer.